Analisis Yuridis Penyimpangan Prosedur Pengadaan Barang dan Jasa di PT Garuda Indonesia - Abdusyahid Naufal Fathullah; Edelweiss Aura Islami; Khumaerastra Fika Salsabila; Finda Pratiwi Yuwono (Universitas Sebelas Maret, 2025)
PT Garuda Indonesia is one of the leading state-owned enterprises (BUMN) in the aviation industry, expected to conduct procurement processes in accordance with the principles outlined in Presidential Regulation No. 16 of 2018 on Procurement of Goods/Services, as well as other relevant laws and government regulations governing BUMN. Given that procurement involves the use of state funds, improper management could result in financial losses for both the state and the company itself. In its procurement process, PT Garuda Indonesia implemented a limited tender method. However, in practice, distortions occurred to favor a predetermined winner, particularly in the procurement of Bombardier CRJ-1000 aircraft. This was achieved through manipulation of assessment criteria and leaking of information to specific parties, violating the fundamental principles of transparency, accountability, and responsibility, which should be upheld in every procurement process. This study aims to identify and analyze the modus operandi used in the aircraft procurement by PT Garuda Indonesia, as well as to examine the irregularities in the procurement of goods and services that may lead to corrupt practices within the company. The research method employed is normative legal research, which focuses on analyzing existing legal norms, including statutory regulations, legal doctrines, and fundamental legal principles, while also evaluating their implementation in practice.The corruption case involving the procurement of Bombardier CRJ-1000 aircraft by PT Garuda Indonesia (Persero) Tbk. (PT GIAA) and the procurement of ATR 72-600 aircraft at PT Citilink stands out as one of the most notorious cases in BUMN procurement history. This case significantly impacted state finances due to data manipulation, lack of transparency, and inconsistencies that deviated from the established criteria. Additionally, the irregularities in this procurement process have fueled public distrust toward Law Enforcement Officials (APH) in handling corruption cases within state-owned enterprises.